Geographic Information System Applications for BeachTourism Area Determination in Bitung City - J. Ch. Kumaat; Markus T. Lasut; Adnan S. Wantasen (Jurnal Ilmiah PLATAX, 2017)
This research was conducted with the aim to determine the suitability of beach tourism area in Bitung city by using Geographic Information System application. This information is necessary to support the provision of geospatial information the beach, so the tourist management in research into more optimum location. Suitability Analysis Zone (spatial) analysis of the suitability of the area is done by using Geographic Information System (GIS), a computer-based geospatial information system involving Arc GIS software 10.1. Based on analysis of the suitability of the area spatially, shows that, for beach tourism area in the area of research, can be divided into 4 (four) classes, namely: (1) land suitability classes by category S1 (Very appropriate) with an area of 376.76 ha (5.87%); (2) land suitability classes with category S2 (Subject) with an area of 262.97 ha (4:10%) (3) land suitability classes with category S3 (In accordance marginal) with an area of 640.48 ha (9.99%) and (4) land suitability classes categories N (Not available) with an area of 5133.79 ha (80.04%) Keywords: Suitability, Area, Zone, Beach Â  Abstrak Penelitian ini dilaksanakan dengan tujuan untuk menentukan kesesuaian kawasan wisata pantai di Kota Bitung dengan menggunakan aplikasi Sistem Informasi Geografis. Informasi ini sangat diperlukan untuk mendukung penyediaan informasi geospasial pantai, sehingga pengelolaan wisata di lokasi penelitian menjadi lebih optimum.Â  Analisis Kesesuaian Kawasan (Spasial) Analisis kesesuaian kawasan dilakukan dengan menggunakan Sistem Informasi Geografis (SIG), yaitu sistem informasi geospasial berbasis komputer dengan melibatkan perangkat lunak Arc GIS 10.1. Berdasarkan hasil analisis kesesuaian kawasan secara spasial, diperoleh bahwa untuk kawasan wisata pantai pada daerah penelitian, dapat dibagi menjadi 4 (empat) kelas, yaitu: (1) kelas kesesuaian lahan dengan kategori S1 (Sangat Sesuai) dengan areal seluas 376.76 ha (5.87%); (2) kelas kesesuaian lahan dengan kategori S2 (Sesuai) dengan areal seluas 262.97 ha (4.10 %) (3) kelas kesesuaian lahan dengan kategori S3 (Sesuai Marginal) dengan areal seluas 640.48 ha (9.99%) dan (4) kelas kesesuaian lahan dengan kategori N (Tidak Sesuai) dengan areal seluas 5133.79 ha (80.04%)